Comparative Analysis of Modifications of RRT Algorithms for Route Planning of a Mobile Robot - Yevsieiev, V. (My University, 2024)
In this paper, a comparative analysis of modifications of the RRT algorithm for route planning of a mobile robot has been carried out. The advantages and disadvantages of such modifications as CW-RRT, BRRT, TG-BRRT, CW-TG-BRRT and H-BRRT in terms of efficiency and complexity of implementation were investigated and compared. The analysis results identify the most appropriate modifications of the RRT algorithm for different mobile robot route planning scenarios, which can be useful for researchers and developers in the field of robotics.
Keywords: Industry 4.0; robotics; comparative analysis; modifications; RRT algorithm